2021
DOI: 10.3390/s21165545
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Ferrofluid Preparation during In-Vitro Culture of Cancer Therapy for Magnetic Nanoparticle Hyperthermia

Abstract: Recently, in-vitro studies of magnetic nanoparticle (MNP) hyperthermia have attracted significant attention because of the severity of this cancer therapy for in-vivo culture. Accurate temperature evaluation is one of the key challenges of MNP hyperthermia. Hence, numerical studies play a crucial role in evaluating the thermal behavior of ferrofluids. As a result, the optimum therapeutic conditions can be achieved. The presented research work aims to develop a comprehensive numerical model that directly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…All of the utilized properties of different materials considered in the current study are mentioned in Table 1 . Nanofluid’s effective properties can be calculated according to the formulas mentioned in reference [ 48 ] and mentioned in Table 1 as well.…”
Section: Methodsmentioning
confidence: 99%
“…All of the utilized properties of different materials considered in the current study are mentioned in Table 1 . Nanofluid’s effective properties can be calculated according to the formulas mentioned in reference [ 48 ] and mentioned in Table 1 as well.…”
Section: Methodsmentioning
confidence: 99%
“…The co‐treatment of the patients with chemo‐radiotherapy and smart drug delivery systems efficiently augmented cytotoxicity against malignant cells, where surgical implantation of the NF mesh into the cancer site could impede cancer relapse. In this regard, one of the most promising solutions in this area is the use of multidrug‐loaded NFs, which can reduce the dosage used while still increasing the effectiveness of chemotherapy (Beola et al, 2021; Liu et al, 2022; Raouf et al, 2021). Nanoengineered implants can then be used to enhance these systems by ensuring controlled and stable release, lowering side effects and boosting medication bioavailability at the target site (Kobayashi, 2011; Rodrigues et al, 2020; Stephen & Zhang, 2021).…”
Section: Smart Chemo‐delivery Systemsmentioning
confidence: 99%
“…When a ferrofluid solution is evaluated on different parameters and the temperature distribution of the system is calculated in space and time, the optimum therapeutic conditions can be found. 140 Regarding MRI, research has shown that IONPs contrast agents are less toxic than other materials such as gadoliniumbased contrast agents. Nevertheless, biocompatibility, biodistribution, and pharmacokinetics should be studied for the future applications of IONPs in clinical stages.…”
Section: Applications Of Ferrofluidsmentioning
confidence: 99%
“…The development of numerical models that correlate the magnetic NP hyperthermia parameters to the thermal response is relevant. When a ferrofluid solution is evaluated on different parameters and the temperature distribution of the system is calculated in space and time, the optimum therapeutic conditions can be found …”
Section: Applications Of Ferrofluidsmentioning
confidence: 99%